Blogging for ICT4D: reflecting and engaging with peers to build development discourse. (4th February 2013) - Ferguson, Julie; Soekijad, Maura; Huysman, Marleen; Vaast, Emmanuelle
Abstract Information and Communication Technology‐enabled Development (ICT4D) discourse relies upon the idea that ICTs can foster development in particular by encouraging wider participation in development initiatives. In this paper, we question how the blogging practices of development professionals shape such ICT4D discourse. Through a combination of interviews and analyses of blog contents, we examine two major purposes of blogging: reflecting upon development practices and engaging with a self‐selected audience. Our analyses reveal that these two purposes were interwoven in ways that contributed to making bloggers' ICT4D discourse innovative but oriented towards a small community of peers rather than a larger audience. Through blogging, development professionals refined their expertise on ICT4D. As they did so, they also generated a personal speaker's corner that primarily attracted like‐minded peers rather than promoting larger participation in ICT4D discourse. This research contributes to the emerging literature on social media practices by showing how blogging practices enable the formation of what a discourse is about, and by highlighting differences between perceived and actual levels of interactions between bloggers and their audience. The paper also adds to the ICT and development literatures by revealing that blogging practices can deepen ICT4D discourse, but that they do not necessarily enhance participation in development. Such insight is crucial for development professionals to develop realistic expectations of blogging for ICT4D.